Community Knowledge and Attitudes Regarding Filariasis: Insights from Papua, Indonesia - Arius Togodly; Evi Sinaga; Ipa Sari Kardi; Miftah Fariz Prima Putra (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The rising incidence of filariasis cases necessitates heightened vigilance, particularly given the limited public awareness about this disease. This study aims to explore community knowledge and attitudes regarding filariasis in Jayawijaya Regency, Papua. Utilizing a sequential explanatory mixed-methods design, the research population comprised all household heads in Itanggen Village, Wolo District. A total of 34 household heads participated as informants, representing each family unit. Data collection employed structured questionnaires followed by in-depth interviews. Findings revealed that 3 filariasis cases was found, accounting for 38.2% (n=13) of respondents demonstrated good knowledge about filariasis, while 61.8% (n=21) showed inadequate understanding. Regarding preventive attitudes, 55.9% (n=19) exhibited positive attitudes toward filariasis prevention, whereas 44.1% (n=15) displayed less favorable attitudes. However, there was no significant relationship between community knowledge and filariasis case (p value=0.729). Also, there was no significant relationship between community attitude and filariasis incident (p value=0.830). These results highlight critical gaps in filariasis knowledge despite moderately positive preventive attitudes, suggesting the need for targeted health education interventions in this endemic region. The study provides valuable baseline data for public health planning in Papua's filariasis control programs.